How SMEs Can Leverage Innovation to Become Global Players - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Small and Medium Enterprises (SMEs) need to realise that being small is only an interim stage on the way to becoming larger enterprises. How SMEs can grow is to leverage on innovation opportunities to transition to the next stage, says Singapore Management University information systems professor Desai Arcot Narasimhalu, speaking recently on “Innovation -- The tracks that can transform SMEs into global players” at the UOB-SMU Entrepreneurship Alliance Centre.